Biomarkers In Pancreas Transplantation April 25, 2016 - Burke, George W (Curr Opin Organ Transplant, 2016)
PURPOSE OF REVIEW: This review analyzes the current biomarkers used in monitoring pancreas transplants (PT), from the simple and time-tested, to more sophisticated, including markers of allo- and auto-immunity, that are likely to play a larger role in future studies. RECENT FINDINGS: Evaluation of allo-immunity includes serum levels of Donor-Specific Antibody (DSA), and, ultimately, PT biopsies with C4d staining. Our center has focused on markers of auto-immunity, including assessment of autoantibodies and autoreactive T cells. We have found that conversion of autoantibodies (including GAD65, IA-2 and ZnT8), or the development of a new positive autoantibody, particularly ZnT8, are associated with recurrence of T1D (T1DR) in the PT. Autoreactive T cells have also been identified in the peripheral blood, PT and peri-PT lymph nodes, that have the potential to mediate human beta/islet cell destruction in vivo. SUMMARY: The monitoring of PT biomarkers, particularly those associated with autoimmunity, has lead to new insights into the pathogenesis of T1D. Progress in the elucidation of mechanisms of autoimmunity may lead to novel therapeutic approaches to both T1DR of the PT and perhaps also new onset T1D.